Community Based Tourism: the reconstruction of identities since the experience of the meeting - Nunes, Mirelle Barcos (2018)
This article aims at the theoretical-conceptual discussion about the idea of identity in the context ofCommunity Based Tourism [TBC]. In this sense, it suggests an interpretation that considers the transformations in the identity dynamics as part of the local patrimony. TBC is an alternative to conventional tourism and has as a brand the community's leading role in the management of tourismactivities. The ways of life are part of the process of reconstruction of identities at each encounter with the other and is present in the elements that constitute the local attractiveness. Recognizing the constant reconstruction of identities is fundamental in the analysis of potential for the development of this type of tourism. We intend this work to be a stimulus to the debate on TBC development processes and identities analysis.